Embracing complexity in Food, Design and Food Design - Jonathan Leroy Biderman (International Journal of Food Design)
Abstract Food Design depends on development of a comprehensive, shared understanding of both Design and Food. This article argues that this emerging, multidisciplinary field must wrestle with several contentious and nuanced issues on the way to establishing itself as a field of inquiry and a community of practice. First, before we can talk about Food Design, we must understand what we mean by ‘design’ and by ‘food’, the latter being a particularly broad, complex and context-variable landscape. Second, the many fields that come to the design table have different sets of values, vocabulary and premises that present a challenge to interdisciplinary collaboration. And third, the universality, diversity and importance of food require that Food Design takes the broadest possible perspective on the food system and be deliberate about seeking out and including every voice and stakeholder in the conversation. There are all sorts of ways that design decisions may affect food and eating behaviour no matter how far removed from food the decisions may seem, and it is the responsibility of a discipline calling itself Food Design to be explicit in its awareness of that. This article concludes with several illustrative examples of the complexity of Food Design.